Pengaruh Pelatihan dan Pengembangan Pekerja terhadap Peningkatan Kinerja Karyawan - Intan, Anak Agung; Gede, I Komang; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study examined the effect of employee training and development on improving the performance of PT employees. Garuda Indah Benoa Pesanggaran Wing in Denpasar. The population of this study was the staff of the PT care department. There are 37 people in the Garuda Indah Benoa Pesanggaran Wing in Denpasar. The sample used in this study was 37, which was determined by the numerical method. Data analysis techniques used in this study are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t-test and F-test. Based on the research results, it can be seen that: (1) Training has a positive and significant effect on employee performance. (2) Staff development has a positive and significant impact on staff performance. (3) Training and staff development simultaneously affect employee performance. After seeing the research results in the future PT care department. Garuda Indah Wing must be able to create training sessions with fun situations such as prize games and others so that employees are happy to participate in the training